1997
DOI: 10.1002/(sici)1098-2361(1997)16:1<17::aid-zoo4>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Body weights of wild and captive lemurs

Abstract: The mean body weight of a species is often used as a summary measure of size in evolutionary and functional studies. Additionally, body weight is often used to assess the health of captive animals. Contrasts of the captive and wild body weights of a species can be used to examine the effects of captivity on the species. We provide an analysis of adult body weight in nine taxa of Malagasy lemurs. We compare weights of wild and captive lemurs and provide analyses of relationships between captive weight variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 14 publications
3
27
1
Order By: Relevance
“…Body mass values based on V. v. variegata. Brockman et al (1987), Cartmill et al (1979), Eaglen (1985), Foerg (1982), Garbutt (1999), Miller (1997, Smith et al (1994), Terranova and Coffman (1997), and records of Duke University Primate Center and Parc Tsimbazaza.…”
Section: Appendix a Life History Data Including Postcanine Dentitiomentioning
confidence: 99%
“…Body mass values based on V. v. variegata. Brockman et al (1987), Cartmill et al (1979), Eaglen (1985), Foerg (1982), Garbutt (1999), Miller (1997, Smith et al (1994), Terranova and Coffman (1997), and records of Duke University Primate Center and Parc Tsimbazaza.…”
Section: Appendix a Life History Data Including Postcanine Dentitiomentioning
confidence: 99%
“…After consideration of both surrogates, lower molar area was chosen because it was a better predictor (higher correlation coefficients) of size when both were tested against actual body masses derived from a smaller sample of captive lemurs and field animals [skull length: r ϭ .601; lower molar area: r ϭ .881] (Glander et al, 1992;Terranova and Coffman, 1997).…”
Section: Statisticsmentioning
confidence: 99%
“…Other studies have shown some evidence of sexual size dimorphism in P. coquereli, P. edwardsi (Ravosa et al, 1993), Propithecus diadema and M. murinus (Kappeler, 1990), although dimorphism in the latter may actually fluctuate throughout the year according to independent changes in male and female body mass (Schmid & Kappeler, 1998). Although the captive environment does not affect adult body mass in lemurs (Terranova & Coffman, 1997), it is unknown whether captivity influences ontogenetic trajectories. However, O'Mara et al (2012) note that whereas absolute growth parameters of captive lemurs may differ from their wild counterparts, relative comparisons among species and between the sexes of a given captive population presumably do not differ from comparisons made on wild populations.…”
Section: Discussionmentioning
confidence: 97%
“…Data on chronological age and body mass were obtained from the Duke Lemur Center's long-term records (Zehr et al, 2014) (Table S1; see King et al, 2005King et al, , 2011 for age estimation methods in the wild population). Studies have found tight correlations between wild and captive primate weights, including those measured at the Duke Lemur Center (Strum, 1991;Leigh, 1994;Terranova & Coffman, 1997). Leigh (1994) reported that across 53 haplorhine species, variation in body weights between wild and captive individuals of the same species was no greater than the variation among wild body weights reported by different sources.…”
Section: Datasetsmentioning
confidence: 99%